Implementation of Occupational Health and Safety in Supporting Service Job Satisfaction of Disaster Volunteers in Banten Province - Gifari, Dikri; Damarwulan, Liza Mumtazah; Anarki, Muhamad (Jagratara: Journal of Disaster Research, 2024)
The role of disaster volunteers is critical in providing essential assistance and support during emergency situations. These volunteers often face hazardous environments and various physical and psychological challenges that can impact their overall health and performance. Ensuring the effectiveness of disaster response efforts necessitates prioritizing the health and safety of these dedicated individuals. This study investigates the influence of Occupational Health and Safety (OHS) practices on the effectiveness of training and the job satisfaction of disaster volunteers. Using quantitative methods, data were collected from disaster volunteers in Banten through questionnaires, interviews, documentation, and literature reviews. The findings indicate that OHS practices significantly enhance the quality and effectiveness of training programs, which in turn increases volunteers' job satisfaction. Effective safety training not only protects volunteers but also contributes to the long-term sustainability of the organization. Additionally, the study reveals that OHS has a significant indirect effect on job satisfaction through training. A healthy and safe work environment directly improves training effectiveness and indirectly contributes to increased job satisfaction. The study concludes that volunteer organizations should strengthen OHS practices and provide comprehensive training to ensure the success of their programs and improve the overall job satisfaction and performance of disaster volunteers. Future research could explore the quality of OHS implementation across different volunteer organizations and examine the long-term effects of OHS and training on job satisfaction and volunteer retention.